Variabilitas Varietas Padi di Lahan Kering Lombok Tengah bagi Pengembangan Pertanian Berkelanjutan - Sanuriza, Irna Il; Jayadi, Irfan; Ihwan, Khaerul; Husain, Pahmi; Risfianty, Dwi Kartika; Dewi, Irma Risvana; Alyaminy, Ishmah Humaidatul Aminah Zaim; Atika, Baiq Naili Dewi (Biocaster : Jurnal Kajian Biologi, 2025)
This study aims to identify the types and distribution of rice varieties cultivated in dry land of Central Lombok as a basis for developing sustainable agriculture in the region. The research method used a randomized block design with several local and superior rice varieties as treatments. The study was conducted with a quantitative descriptive approach at 40 cultivation locations. The results showed that the inpari 32 variety was planted more on dry land in Central Lombok Regency with 19 planting locations, then the inpago 8 variety with 7 locations, the inpari 34 variety with 5 locations, the inpagi variety with 10, inpago 9, and the local bulu variety with 3 locations each. While the planting locations of the inpago 10, inpago 8, inpago 9, inpari 32, and inpari 34 varieties were generally planted in the lowlands. While the local bulu rice was generally planted in the highlands or hills. The results of the study prove that there is significant variation between varieties in their ability to adapt to dry land conditions, with several local varieties showing better resistance to drought stress, water utilization efficiency, and yield stability.